2022
DOI: 10.3389/fsurg.2022.773767
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Evaluation of Cerebral Hemodynamic Changes After Surgery in Adult Patients With Moyamoya Using 2D Phase-Contrast and Intravoxel Incoherent Motion MRI

Abstract: ObjectiveTo explore the feasibility of 2D phase-contrast MRI (PC-MRI) and intravoxel incoherent motion (IVIM) MRI to assess cerebrovascular hemodynamic changes after surgery in adult patients with moyamoya disease (MMD).MethodsIn total, 33 patients with MMD who underwent 2D PC-MRI and IVIM examinations before and after surgery were enrolled. Postsurgical changes in peak and average velocities, average flow, forward volume, and the area of superficial temporal (STA), internal carotid (ICA), external carotid (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Contrarily, the difference in surgical technique resulted in a difference in the CBF change between adult and pediatric patients with moyamoya disease. Gao et al 14 demonstrated that the cerebral blood volume increased after direct revascularization in adult patients with moyamoya disease. Nonetheless, our patients underwent indirect revascularization, and the carotid blood flow did not increase at the end of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the difference in surgical technique resulted in a difference in the CBF change between adult and pediatric patients with moyamoya disease. Gao et al 14 demonstrated that the cerebral blood volume increased after direct revascularization in adult patients with moyamoya disease. Nonetheless, our patients underwent indirect revascularization, and the carotid blood flow did not increase at the end of surgery.…”
Section: Discussionmentioning
confidence: 99%